2001
DOI: 10.1093/oxfordjournals.jbchem.a002959
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Fine Specificity of Several Thomsen-Friedenreich Disaccharide-Binding Proteins with an Effect on Tumor Cell Proliferation

Abstract: Epithelial cancer cells show increased cell surface expression of mucin antigens with aberrant O-glycosylation, notably type I core (Galbeta1-3GalNAcalpha), termed Thomsen-Friedenreich disaccharide (TFD), a chemically well-defined carbohydrate antigen with a proven link to malignancy. Several TFD-binding proteins influence the proliferation of cells to which they bind. We studied the fine specificity of TFD-binding proteins and its relationship with epithelial tumor cell proliferation. Competitive binding assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…ALL is specific for a special GalNAc-containing motif found in O-glycoproteins (26). The T and Tn antigens have been suggested to be used in early detection screening for breast cancer (27)(28)(29) and for hepatocellular cancer (30,31), and they have been considered to be associated with tumors with high risk to metastasize (32). In healthy individuals, these antigens have been also associated with immature cells; moreover, it has been identified that ALL + cell populations possess higher resistance to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…ALL is specific for a special GalNAc-containing motif found in O-glycoproteins (26). The T and Tn antigens have been suggested to be used in early detection screening for breast cancer (27)(28)(29) and for hepatocellular cancer (30,31), and they have been considered to be associated with tumors with high risk to metastasize (32). In healthy individuals, these antigens have been also associated with immature cells; moreover, it has been identified that ALL + cell populations possess higher resistance to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In support of the EIA data for detecting TF-Ag-positive cells, multiple other studies have shown that approximately 80% of human breast carcinomas are positive for TF-Ag [17,[31][32][33][34][35][36], usually by immunohistochemistry. Not all anti-TF-Ag antibodies are useful in immunohistochemistry, and JAA-F11 currently fits in this group, although efforts are being made in our laboratory to develop appropriate fixation methods for immunohistochemistry with JAA-F11.…”
Section: • Radiolabeling Of Jaa-f11 Via the Bolton-hunter Methodsmentioning
confidence: 77%
“…The ER + , PR + and HER2 -cell line T47D also showed a decrease in proliferation at all concentrations of JAA-F11, which reached significance at 2 and 4 μg/ml. PNA (Arachishypogaea) is a lectin that has long been used for the detection of TF-Ag on the surface of carcinoma cells [35,36]. PNA has been shown to increase proliferation of TF-Ag-bearing tumor cells [36].…”
Section: • Radiolabeling Of Jaa-f11 Via the Bolton-hunter Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several TF-binding proteins influence epithelial tumor cell proliferation (Yu et al 1997). TF-disaccharide binding proteins, that stimulate the proliferation of epithelial tumor cell lines, recognize mainly the terminal b-Gal region of b-linked TF antigen, whereas proliferation inhibition is mainly associated by binding to subterminal GalNAc of a-anomeric TF antigen (Irazoqui et al 2001). On tumor cells MUC1 is post translationally modified resulting in incomplete O-glycosylation and presentation of the TF-disaccharide.…”
Section: Introductionmentioning
confidence: 99%